(untitled) (Communications in Computational Physics, 2018)
For numerical simulation of one-dimensional diffraction gratings both in TE and TM polarization, an enhanced adaptive finite element method is proposed in this paper. A modified perfectly matched layer (PML) formulation is proposed for the truncation of the unbounded domain, which results in a homogeneous Dirichlet boundary condition and the corresponding error estimate is greatly simplified. The a posteriori error estimates for the adaptive finite element method are provided. Moreover, a lower bound is obtained to demonstrate that the error estimates obtained are sharp.